PENGARUH KONFLIK PEKERJAAN KELUARGA, STRES KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA PADA KARYAWAN - Pardita, I Putu Indra; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2020)
This study aims to analyze the influence of employee empowerment and family work conflicts, work stress and compensation for job satisfaction in employees of Alaya Resort, Ubud. This study, the method of determining the sample was done by purposive sampling (judgmental sampling) and obtained as many as 62 samples. The analysis technique used is multiple linear regression analysis. The results showed that family work conflict had a negative and significant effect on job satisfaction, work stress and a significant and negative effect on job satisfaction and compensation had a positive and significant effect on job satisfaction on employees of Alaya Resort Jembawan Ubud. Based on these results, the management of Alaya Resort Jembawan Ubud is expected to be more prudent in providing compensation to employees, and management is also expected to improve communication with employees so that they do not feel burdened with excessive work. Keywords: family work conflict, work stress, compensation, job satisfaction .